Using sulfuric acid (H2SO4) for pH adjustment in water treatment - Abd Al-Hussein, Ali Salim (Journal of Petroleum Research and Studies, 2021)
The aim of this paper is to explain the advantages of using sulfuric acid in Qarmat Ali water treatment plant belong to Basrah Oil Company, which produces water for injection into the Rumaila reservoirs. Sulfuric acid is a strong acid providing rapid and effective pH reduction. Maintaining the coagulation pH within the optimum value (6.4) by inject specific value of sulfuric acid to RAW water enhances the clarification performances by reducing the clarified water turbidity to minimum value (5.1). It was preferable for operating at a pH below the saturation pH to prevent the precipitation of minerals such as calcium carbonate which are contributing to blocking the surface filters installed downstream (auto back wash filters) and The clarifiers that cause increased the feed from 500 MBD to 1000 MBD. With a fast and rapid dissociation in Water, Sulfuric acid is an effective and practical way to lower the pH on Qarmat Ali plant which producing in excess of 1,000MBD of export water.